PENERAPAN MEDIA PEMBELAJARAN BERVARIASI DAPAT MENINGKATKAN KUALITAS PEMBELAJARAN MATERI SALING KETERGANTUNGAN DALAM EKOSISTEM PADA SISWAKELAS VIID SMPN 40 SEMARANG - Nadlah, Hj. Izzun (Universitas Negeri Semarang, 2011)
Based on the data analyses problem in the SMPN 40 Semarang there low motivation, only was 20% active in the learning process, and the low of the study result indicate the lower quality of learning happened in the class VII D SMPN 40 Semarang in 2009/ 2010. That this cause there is no variation media in the learning process interaction in the ecosystem. The problems of the classroom action reasearch was “Did application of variation media inthe learning process is to improve the quality learning about interaction in the ecosystem in the class VII D ?“. The goal of the car were to increase: 1. The learning process more then pull, (2) the learning process more then interctive, (3) the quality of learning then more, (4) times efficient and energy. The subject topics were Exretion Systems and Nerve Systems. The Car is held in three cycle : in VII D class with 32 students. The research revealed that the number of students who involve in scientific work from the I-III cycles were 68,5 %, 77.7%and 82% respectively. In the I-III cycle, the number of students who satisfied with the teaching learning process was 89,06%, 90,7%, 99% respectively. The percentage teaher activity from the I-III cycle 56%, 75 %, 89.93 %. There were 59%, 65.625%, 75%, the students test result.